Meat intake and risk of stomach and esophageal adenocarcinoma within the European Prospective Investigation Into Cancer and Nutrition (EPIC) - González, C; Jakszyn, P; Pera, G; Agudo, A; Bingham, S; Palli, D; Ferrari, P; Boeing, H; del Giudice, G; Plebani, M; Carneiro, F; Nesi, G; et al. (2006)
Background: Dietary factors are thought to have an important role in gastric and esophageal carcinogenesis, but evidence from cohort studies for such a role is lacking. We examined the risks of gastric cancer and esophageal adenocarcinoma associated with meat consumption within the European Prospective Investigation Into Cancer and Nutrition (EPIC) cohort. Methods: A total of 521 457 men and women aged 35=70 years in 1 0 European countries participated in the EPIC cohort. Dietary and lifestyle information was collected at recruitment. Cox proportional hazard models were used to examine associations between meat intake and risks of cardia and gastric noncardia cancers and esophageal adenocarcinoma. Data from a calibration substudy were used to correct hazard ratios (HRs) and 95% confidence intervals (CIs) for diet measurement errors. In a nested case-control study, we examined interactions between Helicobacter pylori infection status (i.e., plasma H. pylori antibodies) and meat intakes. All statistical tests were two-sided. Results: During a mean follow-up of 6.5 years, 330 gastric adenocarcinoma and 65 esophageal adenocarcinomas were diagnosed. Gastric noncardia cancer risk was statistically significantly associated with intakes of total meat (calibrated HR per 100-g/day increase = 3.52; 95% CI 1.96 to 6.34), red meat (calibrated HR per 50-g/day increase = 1.73; 95% CI = 1.03 to 2.88), and processed meat (calibrated HR per 50-g/day increase = 2.45; 95% CI = 1.43 to 4.21). The association between the risk of gastric noncardia cancer and total meat intake was especially large in H. pylori-infected subjects (odds ratio per 100-g/day increase = 5.32; 95% CI = 2.10 to 13.4). Intakes of total, red, or processed meat were not associated with the risk of gastric cardia cancer. A positive but non-statistically significant association was observed between esophageal adenocarcinoma cancer risk and total and processed meat intake in the calibrated model. In this study population, the absolute risk of development of gastric adenocarcinoma within 10 years for a study subject aged 60 years was 0.26% for the lowest quartile of total meat intake and 0.33% for the highest quartile of total meat intake. Conclusion: Total, red, and processed meat intakes were associated with an increased risk of gastric noncardia cancer, especially in H. pylori antibody-positive subjects, but not with cardia gastric cancer. © 2006 Oxford University Press.